P8 Cultural fungal mycobiome in non-cystic fibrosis bronchiectasis. (December 2018) - Scadding, AJ; Pashley, C; Monteiro, W; Bhatt, H; Wardlaw, AJ
Abstract : Introduction: Fungi are well known to exist within the lungs chronic respiratory patients but are felt to be pathological when present, difficult to culture and identified infrequently. Cross-sectional sputum analysis was performed on 68 bronchiectasis participants and longitudinal analysis over 18 months on 40 bronchiectasis participants to investigate the hypothesis that sputum fungi are more diverse and prevalent than previously believed. Methods: Data was collected for quality of life measures, airway function and inflammation. Concentrated sputum samples were used for fungal culture on both potato dextrose agar containing chloramphenicol, gentamicin and fluconazole (PGCF) and SceSel+culture media. Results: The 68 participant cohort had a mean age of 69 years, 54.4% were females and 61.8% had never smoked. Thirty three participants did not culture any fungus, 19 had a positive fungal culture and 16 were unable to produce a sputum sample. The participants with a positive sputum culture had significantly more symptoms of cough, breathlessness, sputum production and sputum purulence compared to those with negative fungal cultures. There were no significant differences seen in the SGRQ or LCQ questionnaires, inhaled or oral steroid use, post-bronchodilator spirometry or airway inflammation between the positive and negative culture groups. The proportion of participants with a positive total IgE (>81 kU/L) and Aspergillus specific IgE level (>0.35 kUA/L) was higher in those with negative sputum fungal samples. From the PGCF culture medium the most commonly cultured fungi were the Aspergillus species of which Aspergillus fumigatus was the most commonly cultured. Penicillium species were the next prevalent and other fungi identified included Phanerochaete sordida, Rhizomucor pusillus, Rhizopus microspora, Paecilomyces species, Thermoascus crustaceous, Ceriporia species, Corticiaceae species and Phlebia suberialis. Further fungi were isolated on the SceSel+plates in low numbers. Conclusions: By using a culture method involving concentrated sputum we have proven that fungi are more frequent and diverse in bronchiectasis patients than previously thought. Those with positive fungal cultures had increased respiratory symptoms but otherwise similar investigations to those with negative cultures. Interestingly the group with a positive fungal culture were less likely to have a raised total IgE level or evidence of fungal sensitisation.